Rekonstruksi Kurikulum Pendidikan Muhammadiyah Berbasis Nilai-Nilai Tajdid - Musthofa, Achmad; Anggra, Dwy; Al-Azhari, Yahya Husein; Halili, Heri Rifhan (Educational Research Center, 2026)
This research aims to analyze the concept of tajdid in Muhammadiyah education and formulate a model of curriculum reconstruction based on values. The change in the curriculum in Muhammadiyah reflects the tendency to adopt a technocratic national curriculum. This study uses a qualitative approach with a conceptual-critical study design combined with historical and philosophical studies. Data analysis was carried out using qualitative content analysis and thematic analysis sourced from books, articles from SINTA-indexed national journals. 1. Muhammadiyah education is expected not to be closed to change, but still maintain its identity and basic values that are its characteristics. 2. Muhammadiyah education functions as a strategic instrument for the formation of a progressive Muslim generation with character. 3. The reconstruction of this curriculum is a strategic step to maintain the quality, competitiveness, and uniqueness of Muhammadiyah education in the midst of the dynamics of national and global education. These findings show that tajdid values in Muhammadiyah education are not just normative discourses, but must be the main paradigm in curriculum development.